CONDUCTING ACTION RESEARCH IN INDONESIA: ILLUSTRATIONS AND IMPLICATIONS - Anne Burns; Dewi Rochsantiningsih (Universitas Katolik Indonesia Atma Jaya, 2006)
In this article we discuss some of the key features of action research (AR) and how it can be applied in the educational context. We then describe how principles of AR were used in the Indonesian context with ten high school teachers as a professional development experience to encourage the teachers to reflect on their teaching and to introduce changes into their classroom practices. The teachers reported that, in contrast to previous professional development, AR provided them with a powerful means of professional growth as it was closely related to their own teaching situations. It also created changes and innovations in their teaching practices that they believed led to more effective classroom activities and teacher-student interactions. Nevertheless, they also reported various difficulties associated with undertaking research in the classroom. We conclude the article by presenting a case study to illustrate in more detail how AR was conducted by one of the teachers and what changes occurred in her teaching. The article also draws out implications of the study for teacher education in Indonesia. Keywords: action research, Indonesian context